Foraging Activity and Dietary Spectrum of the Argentine Ant (Hymenoptera: Formicidae) in Invaded Natural Areas of the Northeast Iberian Peninsula (Environmental Entomology,, 2007)
We analyzed the foraging activity and the dietary spectrum of the Argentine ant (Linepithema humile Mayr) and select native ants on cork oaks from Mediterranean open cork oak (Quercus suber) secondary forests. The study areas included invaded and noninvaded zones in close proximity. The Argentine ant's daily foraging activity was correlated to the abiotic factors studied, whereas the seasonal foraging activity was related not only to the variations in the average air temperature, but also to the trophic needs of the colony. Argentine ant workers focused their attention on protein foods during the queens' oviposition periods and during the larvae development phase, and on carbohydrate foods, such as honeydew, when males and workers were hatching. There were no significant differences over the entire year in the quantity of liquid food collected by the Argentine ant workers in comparison with the native ants studied. The solid diet of the Argentine ant on cork oaks is composed of insects, most of which are aphids. Our results have clear applications for control methods based on toxic baits in the invaded natural ecosystems of the Iberian Peninsula.

Long-term consequences of the alteration of the seed dispersal process of Euphorbia characias due to the Argentine ant invasion (ECOGRAPHY, 2005)
The alteration of the seed dispersal process due to the Argentine ant invasion and its consequences on emergence, recruitment, distribution, and survival of seedlings of Euphorbia characias were analyzed. The study was carried out in two zones of Mediterranean cork-oak secondary forest, one invaded by L. humile and the other non-invaded. Two cohorts of E. characias seedlings (those emerged in 2001 and those emerged in 2002) were studied in three study plots in each zone. The level of seed loss due to lack of viability, parasitizing, and vertebrate predation did not differ between the two zones. The mean seed sowing depth was lower in the invaded zone (13.5 mm) than in the non-invaded zone (22.4 mm). This depth difference implies a longer time needed for seedlings to emerge in the non-invaded zone but not a different emergence percent under laboratory conditions. In the field study plots seedling recruitment did not differ between the two zones, probably due to the trade-off between the differences in the initial number of seeds released (higher in the non-invaded zone) and the different emergence proportions (higher in the invaded zone). As for the spatial characteristics of emerged seedlings, no differences in the mean seedling distance to the nearest inflorescence or to the nearest seedling or in the pattern of seedling distribution were found between zones. Seedling survival was assessed once a month until they had reached maturity or until all of them had died. The median seedling survival time was similar between the invaded and the non-invaded zones. Survival curves also did not differ between zones. The present study suggests a functional equivalence of the Argentine ant after the replacement of the native ant species. Despite the initial differences found, the final reproductive success of E. characias was not altered after the invasion. However, the case of E. characias seems unlikely to be the rule, and the seed dynamics of other species may be altered, i.e. increased or decreased, and thus positively or negatively affected by the invasion.

Structure of ground-foraging ant assemblages in relation to land-use change in the northwestern Mediterranean region (Biodiversity and Conservation, 2003)
The abandonment by humans of marginal and less productive zones signiﬁes an important change in land use in North Mediterranean agroecosystems. Human perturbations have led to a highly diversiﬁed landscape, with a mosaic made up of patches of land at different stages of succession, from cultivated ﬁelds to closed forest. Our aim here is to characterize ant assemblages and their functional groups in response to these land-use changes. This progressive abandonment results in an initial increase in ant richness and abundance, which can reach high levels if the succession proceeds as far as woodland. In terms of the ant functional groups, this land-use change implies: (1) the appearance of Subordinate Camponotini; (2) an increase in Generalized Myrmicinae, Cryptics and Cold-climate specialists in terms of ant species richness, overall abundance and, for Generalized Myrmicinae and Cryptics, an increase in abundance percentage; (3) a decrease in percentage abundance of Opportunists; (4) a progressive decrease in species richness as well as overall and percentage abundance of Hot-climate Specialists throughout the transformation from crops to woodlands; and (5) an initial increase of Dominant Dolichoderinae followed by a decrease in ant species richness, overall abundance and percentage abundance. Using the ant functional group approach for the clearly separate stages of the regeneration process is a promising method for comparing responses of ant communities to human land use.